Identification of a novel, alpha2-fucosylation-dependent uptake system in highly proliferative cells. Issue 1 (February 2015) - Aldi, Silvia; Capone, Antonietta; Giovampaola, Cinzia Della; Ermini, Leonardo; Pianigiani, Elisa; Mariotti, Giancarlo; Rosati, Floriana
Highlights: Fucosylated glycans have been explored outside and inside the cells by AAL and LTL. Both lectins localize glycans only into Golgi apparatus in normally growing cells. LTL localize glycans in tubular structures in highly proliferative cells. LTL positive glycans are also present outside proliferative cells. LTL can be internalized by the proliferative cells through the tubular structures. Abstract: In this paper we describe a new structure present in highly proliferative cells and absent in cells with normal growth potential. We used cultured bovine venular endothelial cells (CVEC) as examples of high proliferation, and dermal fibroblasts of a primary culture as examples of normal proliferation. The structure, consisting of tubules radiating from the nuclear region to the tips of cell protrusions, was revealed by its strong positivity to the fucose-binding lectin from Lotus (LTL) that prefers glycans with alpha-1, 2-linked fucose. Another fucose-binding lectin that prefers glycans with alpha-1, 6-linked fucose was instead found to localize glycans exclusively in Golgi complexes. LTL binding sites were also found at the surface of CVEC in a restricted region close to the nucleus. The role of alpha-1, 2-linked fucose in forming or maintaining the tubules was confirmed by the fact that down-regulation of the fucosyltransferases FUT1 and FUT2 resulted in disappearance of the tubular structure. LTL also proved able to penetrate the cells through the tubular structures up to the nuclear region and to inhibit proliferation. Endostatin was also found to massively penetrate the cells in the tubular structures in control cells but not in FUT1/2 depleted cells. In cells of a first passage primary culture of dermal fibroblasts the tubular LTL-positive structure was absent as well as the LTL-positive sites at the external surface, and both fucose-binding lectins were found to exclusively localize glycans in Golgi complexes. Tubules were again found progressively in fibroblasts derived from repeated passages, where faster growing cells predominate. Disappearance of LTL-positivity in Golgi complexes paralleled appearance of LTL-positive tubules. The role of Golgi complexes in forming the tubules is discussed.